Impact of two tillage practices on selected soil properties, growth and yield of maize on an ultisol - Komolafe, Oluwatosin (2022)
This study investigated the effect of two tillage practices on maize yield and growth, and selected soil properties of an Ultisol of Osun State in Nigeria. This was aimed at selecting an appropriate tillage practice for crop growth and soil maintenance. The study was divided into two experimental plots during the early and late cropping season in 2014. The first plot was manually cleared to have zero tillage while the second plot was plowed twice and harrowed once for conventional tillage. Each plot had three blocks (23.0 m x 2.5 m) with an alley of 1.0 m between blocks and 1.0 m within plots. Three seeds of the test crop were a distance of 75 cm x 50 cm per hill and each plot weeded manually at two weeks intervals till harvest. The selected soil physical and chemical properties and plant growth parameters were collected and determined using standard method after each cropping season. At the end of the experiment zero tillage, had the highest plant height and soil values compared to conventional tillage. Zero tillage also had higher soil chemical values when compared to conventional tillage. The grain yield showed a significant difference between the tillage practices. Zero tillage had a higher yield (1.71 t/ha) when compared with conventional tillage (0.97 t/ha). The study concluded that zero tillage was a better alternative for crop growth and soil maintenance of an Ultisol.